The level of aerobic capacity in elite youth soccer players and its comparison in two age categories - Teplan, J.; Maly, T.; Zahalka, F.; Hrasky, P.; Kaplan, A.; Hanus, M.; Gryc, T. (Journal of Physical Education and Sport, 2012)
The main purpose of this study was to compare total run distances, which is an indicator of a player`s aerobic capacity, in U16 and U17 junior categories in intermittent recovery Yo-Yo test. The secondary purpose was to find out physiological responses (maximum heart rate and maximum oxygen consumption value) in Yo- Yo intermittent recovery test (Yo-Yo IRT). Material and method The monitored groups consisted of U16 category (n = 14, age = 15.5 ± 0.2 years, body height = 173.6 ± 7.8 cm, body weight = 64.5 ± 6.8 kg) and U17 category (n = 16, age = 16.4 ± 0.3 years, body height = 178.8 ± 6.4 cm, body weight = 70.6 ± 8.3 kg) players. To examine maximum aerobic capacity, Yo-Yo IRT was used. This field test is focused on assessment of run distance, VO2max and heart rate (HR). For statistical verification of research data, we used parametric t-test for independent samples, same variances, which were verified by Leven`s test for equality of variances. Probability of rejecting null hypothesis was set at the level of p<0.05. Results The average run distance in U16 players 1594.3 ± 287.1 m and U17 = 2002.5 m ± 331.9 m. This difference was statistically significant t28 = -3.58; p<0.01 and equalled 20.4 %. The maximum value of heart rate (HRmax) in the younger players was HRmaxU16 = 198.9 ± 6.6 beat .min-1and HRmaxU17 = 194.8 ± 6.8 heart rate.min-1. The maximum oxygen consumption value (VO2max) was VO2maxU16 = 49.4 ± 2.7 ml.kg-1.min-and VO2maxU17 = 52.8 ± 3.2ml.kg-1.min-1 Conclusions These results are in accordance with theoretical knowledge which indicates that the players are able to achieve better performance in Yo-Yo IRT with increasing age or quality of competition.